Analisis Dan Perancangan Sistem Informasi Penanganan Keluhan Masyarakat Berbasis Web (Studi Kasus: Pemerintah Kabupaten Sidoarjo) - Fikri Rizky Adinata; Widhy Hayuhardhika Nugraha Putra; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Government of Sidoarjo has the objective to improve the quality of innovative and equitable public services to the society which is a public complaint service that is sheltered by the Public Complaints and Service Center (P3M). One of the society's features to complain is the website that has been provided by P3M Sidoarjo Regency. However, the website is less attractive to society because it has many problems. one of them is the complaints are difficult to trace, there are no supporting features in making complaints and there is no feature for two-way communication in complaints that have been made. from some of these problems, society prefers to make complaints through social media. from some of these problems the society prefer to make complaints through social media, this makes complaints not recorded properly. Based on problem, the analysis and design of an information system are needed to resolve the problem. the system design process is created using Object-oriented analysis and design with UML modeling. the results of the system design are evaluated using the Traceability Matrix and usability testing. requirements analysis produces 32 functional requirements and 1 non-functional requirement and 12 use cases, in the system design made 4 controller classes and 10 model classes, at the evaluation stage using traceability matrix shows all the results of the system design can be traced to the requirements analysis and business process modeling and Evaluation using usability testing results in an average success rate of 97% and an average time-based efficiency of 0.03 tasks/second.